Analisis Pendapatan Usahatani Padi Penguna dan Bukan Penguna Usaha Pelayanan Jasa Alsintan (UPJA) di Kecamatan Rogojampi Kabupaten Banyuwangi (Jurnal Agribisnis dan Agrowisata, 2025)
Income Analysis of Rice Farming Users and Non Users of Alsintan Service Business (UPJA) in Rogojampi District, Banyuwangi Regency. Alsintan Service Business (UPJA) is one way to accelerate the mechanization of agricultural machinery in increasing rice farming production. Farmers have not fully utilized the services of UPJA and have switched to private leasing parties in the mechanization of agricultural machinery due to the consideration of obtaining greater farm income. The purpose of this study was to analyze the amount of income and differences in income of rice farming users and non-users of UPJA. This research was conducted in Rogojampi District, Banyuwangi Regency, East Java Province. Methods of data collection were carried out by direct interviews with respondents, observation and literature study. Sampling with non-probability sampling technique. Data analysis used is income analysis and Mann Whiteney test. The results showed that UPJA users earned a higher income per hectare than non-users of UPJA, namely Rp24,700,612, while non-users of Rp20,316,819. The difference in farm income between farmers using UPJA and farmers who are not using UPJA with the Mann Whiteney test obtained a significance value (Asymp. Sig. (2-tailed) greater than 0.05, which is equal to 0.233 so it can be concluded that there is no difference in income between farmers using UPJA and farmers who are not UPJA users. Based on the research results, it is hoped that the government will distribute alsintan in accordance with the conditions of the farmer's land and extension workers in coordination with the Gapoktan chairman regarding the use of alsintan which provides benefits in the form of time, labor and cost efficiency in farming.
Keywords: income; rice farming; Alsintan Service Business (UPJA)